(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The company management is inextricably connected with researching of financing sources of economic activity. Diversification of financing sources relies on using equity capital as well as loan capital. The choice of loan capital is related with researching of effective financing sources, taking into account the costs of their obtaining. The aim of this article is presentation of the applying procedure for subsidization by companies on the example of Sectorial Operational Program “Fishing and fish processing 2004-2006”. The article shows also the way of analysis of planning investment projects based on the costs, which are connected with subsidization’s obtaining